Penerapan Kafaah dalam Perkawinan Masyarakat Desa Sangiang Kecamatan Wera Kabupaten Bima (Studi terhadap Keharmonisan Rumah Tangga): Implementation of Kafaah in Maririage in Sangiang Village, Wera District, Bima Regency (Study of Household Harmony) - Resnawati, Resnawati; Lalu Muhammad Nurul Wathoni (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This research aims to identify and find out how the people of Sangiang Village, Wera District, Bima Regency understand the concept of kafaah in marriage and find out how the influence of kafaah in forming a sakinah family in this community. This research uses qualitative methods with an empirical research approach. The data collection methods used were observation, interviews and documentation. The results of this research show that: first, the practice of understanding the concept of kafaah in marriage looks at the criteria of tahora wati dou (behavior), londora ndoi ndaina (family relationships), sama douma ncoki sama dou ma ntau wara (wealth factor), and school (education). Second, the influence of kafaah in forming a sakinah family is influenced by several things, namely taho nuntu ra nggahina (good communication), cua loa ka ao (understanding or understanding each other), and wati disa na hanta rima ra edi (not committing violence against one's partner). The results of this research also show that the people of Sangiang Village, Wera District, Bima Regency who apply kafaah in marriage show that their households are harmonious, characterized by several factors explained above.